Social data analytics - Beheshti, Amin; Ghodratnama, Samira; Elahi, Mehdi (BOCA RATON: CRC PRESS, 2022)
"The book provides an introduction to social data analytics along with its challenges and opportunities. It chiefly focuses on concepts, techniques and methods for organizing, curating, processing and analyzing big social data: from text to image and video analytics. It also provides novel techniques in storytelling with social data to facilitate the knowledge and fact discovery. It covers a large body of knowledge on to help practitioners and researchers understand the underlying concepts, problems, methods, tools and techniques involved in modern social data analytics. The book provides researchers with an introduction to these fields by comprehensively classifying the current state of research, by describing in-depth techniques and methods, and by highlighting future research directions. Lecturers will find a wealth of material to choose from for a variety of courses, ranging from undergraduate courses in data science to graduate courses in data analytics. The key highlights of the book are that it covers a large body of knowledge to help practitioners and researchers understand the problems, concepts, methods and tools involved in modern social data analytics. It also includes a wealth of material to choose from for courses in data science and analytics. The book provides real-world applications of social data analytics, including: Sales and Marketing, Influence Maximization, Situational Awareness, customer success and Segmentation, and performance analysis of the industry"--
Includes bibliographical references and index.
Keywords: Social media; Text processing (Computer science); Information visualization; Data mining